Cele două liste (un comentariu la Două loturi de I.L. Caragiale) - Mihai Iovănel (Revista de Istorie și Teorie Literară)
In this essay I reread Două loturi, a classical text of I.L. Caragiale, trying to elucidate the meaning of its paradoxical ending by explaining the ideological and economical implications of the lottery topic used by Caragiale in relation to such notions as chance or bad luck.